Uji Aktivitas Antibakteri Ekstrak Daun Ciplukan (Physalis Angulata L.) Terhadap Bakteri Bacillus subtilis - Susanti, Susanti Delina; Yudi Arina; Tri Oktarina; Meisy Erpa (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
Ciplukan (Physalis Angulata L.) is a traditional medicinal plant from the Solanaceae family that is often used to cure skin infections. Ciplukan leaves (Physalis Angulata L.) have antimicrobial activity in preventing acne. The flavonoid and saponin content in ciplukan leaves plays an important role as cell wall permeability and causes cell death. Ciplukan leaves have also been shown to contain Flavonoid, saponin, tannin, and glycoside compounds. Objective: From this study - to determine the antibacterial activity of Bacillus Subtilis using ciplukan leaf extract (Physalis Angulata L.) with the maceration method, - to determine at what concentration the ciplukan leaf extract (Physalis Angulata L.) can inhibit the growth of Bacillus Subtilis bacteria. Method: This study used the maceration method and the disc method. The design of this study was to see the antibacterial activity test of Ciplukan leaf extract (Physalis Angulata L.) against Bacillus subtilis bacteria. Results: Ciplukan leaf extract (Physalis Angulata L.) has an inhibition zone against the growth of Bacillus subtilis bacteria with a concentration of 25% of 16.23 mm which is considered moderate, a concentration of 30% of 17.24 mm which is considered moderate, a concentration of 35% of 18.22 mm which is considered moderate, a concentration of 40% of 19.23 mm which is considered moderate, a positive control of ciprofloxacin of 20.21 mm which is considered strong.